2017
DOI: 10.1007/s00101-017-0383-4
|View full text |Cite
|
Sign up to set email alerts
|

Additive notärztliche Maßnahmen beim traumaassoziierten Herz-Kreislauf-Stillstand

Abstract: The percentage of patients who might benefit from additive treatment implemented in tCPR efforts was shown to be equal between the local situations in Leipzig and Chemnitz compared to previous reports in Berlin. A need for optimizing the professional resuscitation process still remains as not all reversible causes were appropriately addressed. Further training and education should intensively address the mentioned deficits and continuous awareness of necessary additional medical procedures in the preclinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 32 publications
0
1
0
3
Order By: Relevance
“…Many studies have shown that that early causes of death in the acute care phase are associated with emergency measures 13 . Thus, investigating mechanical complications of emergency procedures might help to change practice patterns in order to reduce preventable deaths, which are reported ranging from 12.3 to 58% in trauma patients 14 17 . In one study with severe trauma patients, 56% of endotracheal tubes, chest tubes and CVCs were documented by postmortem computed tomography (CT) to be misplaced 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that that early causes of death in the acute care phase are associated with emergency measures 13 . Thus, investigating mechanical complications of emergency procedures might help to change practice patterns in order to reduce preventable deaths, which are reported ranging from 12.3 to 58% in trauma patients 14 17 . In one study with severe trauma patients, 56% of endotracheal tubes, chest tubes and CVCs were documented by postmortem computed tomography (CT) to be misplaced 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Dabei stellte sich in den entsprechenden Untersuchungen ein relevanter Anteil der Todesfälle als potenziell vermeidbar dar, wenn bereits präklinisch eine suffiziente Traumaversorgung erfolgt wäre [1]. Nicht entlastete Spannungspneumothoraces wurden dabei als potenziell reversible Ursache vergleichbar häufig wie eine nicht entlastete Perikardtamponade festgestellt [1,2]. Im Jahr 2015 fand das Thema "traumatisch bedingter Herz-Kreislauf-Stillstand" ("traumatic cardiac arrest" [TCA]) erstmalig Einzug in die aktualisierten Reanimationsleitlinien des European Resuscitation Council (ERC; [3]).…”
Section: Hintergrundunclassified
“…Hochgerechnet auf die Gesamtbevölkerung in Deutschland entspreche dies bei allen statistischen Ungenauigkeiten und regionalen Unterschieden mehr als 80 potenziell geretteten Menschenleben pro Jahr [6,9]. In einer Folgeuntersuchung konnten Ondruschka et al zusammen mit selbigen Autoren für die Jahre 2011-2017 in den Städten Leipzig und Chemnitz im Verhältnis zur Einwohnerzahl sogar eine noch höhere Inzidenz von traumatischen Perikardtamponaden und infolge traumatischen Kreislauf-stillständen mit konsekutiver Indikation einer prähospitalen Notfallthorakotomien aufzeigen [20]. Bemerkenswert ist dabei, dass seitens der Autoren als Indikation für eine Notfallthorakotomie ausschließlich Perikardtamponaden in Erwägung gezogen wurden.…”
Section: Verlaufunclassified